Solving the scattering of N photons on a two-level atom without computation - Alexandre Roulet; Valerio Scarani (New Journal of Physics, 2016)
We propose a novel approach for solving the scattering of light onto a two-level atom coupled to a one-dimensional waveguide. First we express the physical quantity of interest in terms of Feynman diagrams and treat the atom as a non-saturable linear beamsplitter. By using the atomic response to our advantage, a relevant substitution is then made that captures the nonlinearity of the atom, and the final result is obtained in terms of simple integrals over the initial incoming wavepackets. The procedure is not limited to post-scattering quantities and allows for instance to derive the atomic excitation during the scattering event.